2011
DOI: 10.1007/s10109-011-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

The welfare benefit of a home’s location: an empirical comparison of spatial and non-spatial model estimates

Abstract: This article compares results from non-spatial and new spatial methods to examine the reliability of welfare estimates (direct and multiplier effects) for locational housing attributes in Seattle, WA. In particular, we assess if OLS with spatial fixed effects is able to account for the spatial structure in a way that represents a viable alternative to spatial econometric methods. We find that while OLS with spatial fixed effects accounts for more of the spatial structure than simple OLS, it does not account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…These two reasons may lead to a spatial component of land use data, which has the tendency to deviate from the often-assumed independence of observations [56]. From an econometric perspective, the incorporation of spatial dependence into the prediction of land use choices can improve model’s goodness-of-fit, reduce the probability of omitted variable bias, provide better model coefficient estimates and improve the analysis of marginal effects [57,58,59,60]. …”
Section: Literature Reviewmentioning
confidence: 99%
“…These two reasons may lead to a spatial component of land use data, which has the tendency to deviate from the often-assumed independence of observations [56]. From an econometric perspective, the incorporation of spatial dependence into the prediction of land use choices can improve model’s goodness-of-fit, reduce the probability of omitted variable bias, provide better model coefficient estimates and improve the analysis of marginal effects [57,58,59,60]. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Spatial interactions in house or land markets have been well recognized in at least two ways. The first regards the actual workings of the real estate market, in which the sale prices of nearby properties are often used to guide the price of a property for sale (e.g., Can 1992;Koschinsky, Lozano-Gracia, and Piras 2012). The second is related to the interacting decision-making process like house maintenance or repairing decisions among householders (Can and Megbolugbe 1997).…”
Section: Application Of the Hsar Modelmentioning
confidence: 99%
“…Physical factors including floor areas, a building's age, and the number of stories, bedrooms, and bathrooms, have proven to be significant to varying degrees [6][7][8][9][10][11][12]. Jun and Kim [12], for instance, found that both floor areas and the number of stories have positive impacts on the monthly rent charged for apartments; the age of a dwelling, however, influences rent negatively.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, academics have investigated the effects of these attributes. They encompass access to green and open spaces, access to amenities such as parks, playgrounds, sea views, watercourses, and landscapes, and environmental conditions such as noise and air quality levels [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%